1976
DOI: 10.1126/science.1251193
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemic Principles Isolated from Euphorbiaceae Plants

Abstract: Extracts of Euphorbia esula L. and Croton tiglium L., two members of the Euphorbiaceae which have been used widely in folk medicine for treating cancers, showed antileukemic activity against the P-388 lymphocytic leukemia in mice. Systematic fractionation of the extract of Euphorbia esula L. led to characterization of a major antileukemic component as the new diterpenoid diester, ingenol 3,20-dibenzoate. Similar fractionation of Croton oil led to characterization of phorbol 12-tiglate 13-decanoate as an active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
80
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(85 citation statements)
references
References 5 publications
1
80
0
4
Order By: Relevance
“…The diverse composition of the latex, which includes toxic compounds as well as other interesting and potentially bioactive molecules such as diterpenes and triterpenes could be responsible for antibacterial and anti-fungal activity (Kupchan et al, 1976;Ferreira et al, 2002). In this study it was observed that E. antiquorum latex possess mild antibacterial property and our finding comply with previous study of (Sumathi et al, 2011).…”
Section: Resultssupporting
confidence: 82%
“…The diverse composition of the latex, which includes toxic compounds as well as other interesting and potentially bioactive molecules such as diterpenes and triterpenes could be responsible for antibacterial and anti-fungal activity (Kupchan et al, 1976;Ferreira et al, 2002). In this study it was observed that E. antiquorum latex possess mild antibacterial property and our finding comply with previous study of (Sumathi et al, 2011).…”
Section: Resultssupporting
confidence: 82%
“…In connection with antileukemia, the allamandin derivatives which are extracted with water and/or ethanol from Allamanda catharica (Apocynaceae) showed significant activity in vivo against the p-388 leukemia in the mouse (Kupchan et al, 1976).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, latex is indicated for both prevention and treatment of malignant neoplasias (leukemia, skin cancer, and digestive tract cancer), and is also used as an immunomodulator, a healing agent, and in diabetes treatment (Ortêncio, 1997). Some studies performed using other species from the genus support the antitumor and angiogenic activity observed (Kupchan et al, 1976;Schroeder et al, 1980;Hubert and De-Thé, 1982;Yan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%